Pengaruh Personal Branding Sumber Daya Insani Perbankan Syariah Terhadap Digitalisasi Banking di Era Industri 4.0 - Zhara Hafizha; Tuti Anggraini (Jurnal Ilmiah Ekonomi Islam, 2023)
Abstract This study aims to determine the relationship between personal branding of banking human resources and digitalization of banking in the era of the industrial revolution 4.0 at BSI KCP Perbaungan. Due to this era of digitalization, digital banking emerged which had an impact on reducing employees. Because this phenomenon will increase the market for high labor competition, this will support increasing personal branding to survive in today's digital era. The sample in this study was 30 people, including the saturated sample because the entire population was used as the sample. The analysis used is simple regression analysis. The results of the study show that there is a relationship between variables. Personal branding variables have an effect of 31.1% on Banking Digitalization. The remaining 68.9% is caused by other variables outside the variables not involved in this study. Based on the regression calculation, the tcount value for the personal branding variable is 3,557. this value is greater than the ttable value of 2.048. Because tcount > ttable, it can be concluded that there is a significant relationship between Personal branding and Digitalization banking at BSI Kcp Perbaungan. So by testing the hypothesis then H1 is accepted and H0 is rejected. Where it can be interpreted that there is an influence between the personal branding variable (X) on digitalization of banking at Bank BSI Kcp Perbaungan (Y).